2022
DOI: 10.1177/2473974x221119150
|View full text |Cite
|
Sign up to set email alerts
|

Cost of the Otolaryngology Residency Application Process: Comparison With Other Specialties and Equity Implications

Abstract: Objective This study aims to assess trends in applicant-reported costs of the otolaryngology residency application process between 2019 and 2021 and evaluate the impact of application costs on number of interview offers. Study Design Cross-sectional study. Setting US allopathic and osteopathic medical schools. Methods Survey data from applicants were obtained from the Texas STAR database (Seeking Transparency in Application to Residency) for the years 2019 to 2021. Outcomes included total cost, interview cost,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Although virtual away rotations cannot reproduce all aspects of the in‐person experience, they offer a more affordable and more equitable alternative. In a recent cost analysis of the otolaryngology residency application process, we found an average decrease in spending of $5669 per applicant in the 2020 to 2021 application cycle, presumably due to a lack of in‐person away rotations and interviews that year 23 . Both applicants and programs have emphasized the ability for virtual away rotations to help level the playing field for applicants from economically disadvantaged backgrounds, those without a home program, those who identify as URiM, and those who are IMG 3,24,25 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although virtual away rotations cannot reproduce all aspects of the in‐person experience, they offer a more affordable and more equitable alternative. In a recent cost analysis of the otolaryngology residency application process, we found an average decrease in spending of $5669 per applicant in the 2020 to 2021 application cycle, presumably due to a lack of in‐person away rotations and interviews that year 23 . Both applicants and programs have emphasized the ability for virtual away rotations to help level the playing field for applicants from economically disadvantaged backgrounds, those without a home program, those who identify as URiM, and those who are IMG 3,24,25 .…”
Section: Discussionmentioning
confidence: 84%
“…In a recent cost analysis of the otolaryngology residency application process, we found an average decrease in spending of $5669 per applicant in the 2020 to 2021 application cycle, presumably due to a lack of in-person away rotations and interviews that year. 23 Both applicants and programs have emphasized the ability for virtual away rotations to help level the playing field for applicants from economically disadvantaged backgrounds, those without a home program, those who identify as URiM, and those who are IMG. 3,24,25 Our findings suggest that virtual away rotations might help applicants with interviewing and matching at a program of interest if virtual rotations are offered.…”
Section: Discussionmentioning
confidence: 99%
“…Costs associated with residency applications and away rotations in surgical subspecialities have been investigated in the literature and evidence shows that the costs for applying to certain surgical subspecialties is higher than other subspecialties [ 13 , 16 , 20 , 29 , 30 ]. Specifically, Gordon et al used the Texas STAR database to compare the costs of students applying to competitive surgical residencies, and the authors found application costs to vary depending on subspeciality and geographic region [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Texas STAR survey response rate averages 40% (unable to calculate for 2017, 47% in 2018, 38% in 2019, 47% in 2020). Several prior studies have utilized this database to evaluate applicant characteristics, expenditures, and success with matching into a surgical residency [ 13–21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Prepandemic data suggest that otolaryngology applicants who complete away rotations might improve their match outcomes at programs where they spent time; 32.7% of applicants matched to the program where they completed an away rotation, and 48.8% of applicants who ranked a program where they completed an away rotation first on their rank list matched there 5 . However, away rotations incur costs estimated at $1600 to and $2500, 6,7 which might deter economically disadvantaged applicants from participating 8‐12 …”
mentioning
confidence: 99%